Teachers’ Perceptions about Community Participation on School-Based Management in Meghalaya State - Singh, Ayushi; Tyagi, Ankur; Singh, Virendra Pratap (THE PRIMARY TEACHER, 2022)
The study presents teachers’ perceptions about community participation in school-based management practices in elementary schools as envisaged under RTE Act 2009. The research was conducted in a tribal concentrated rural area of Meghalaya State. The study took an evaluative approach, so data were gathered through a schedule for teachers covering Act provisions, as well as focus group discussions with stakeholders. The sample of data sources for gathering information were teacher’s consisting of head-teachers, primary teachers, and upper primary teachers. The quantitative information was analysed and expressed in percentages and statistical figures. The qualitative information was collected through semi-structured data items from teachers, and an open coding method was applied to analyse the same. The results of a study on teachers’ perceptions of community participation concluded with a positive and motivating picture. However, to attain the goals of the Act, more stringent measures should be taken by the State, especially in empowering the community through SMC members to implement various academic and non-academic programmes in the elementary schools.